‘Revival’ et transformation spirituelle chez les Inuit de l’Arctique central canadien - Laugrand, Frédéric (Terrain, 2016)
The author analyses the notion of “spiritual transformation” in the context of the presence of evangelical groups like the Canada Awakening Ministries (CAM) among the Inuit. The CAM, who have been established among the Inuit in both the Nunavik and the Nunavut for a long time, have developed close relationships with pastors from the Fiji Islands. They perform various rites of exorcism and earth-healing rituals whose idiom, the author suggests, is recognized by the Inuit although their traditions are quite different. Nowadays these traditions face many challenges: the strong interest in the environment is confronted with the exploitation of local resources and the discussions on global warming.